Commanding heights the battle for the world economy - Yergin, Daniel; Stanislaw, Joseph ([Boston, Mass.] WGBH Boston Video, 2003)
Presents the inside story of the new global economy in a narrative film footage of stories and interviews of world leaders and thinkers of twenty different countries in five continents of the world.
Based on the book by Pulitzer Prize winner Daniel Yergin and Joeph Stanislaw.
Narrator: David Ogden Stiers ; music, Paul Foss ; episode 3 writer, producer, director: Greg Barker ; executive producer for Heights Productions: Sue Lena Thompson and Daniel Yergin ; executive producer for WGBH: Michael Sullivan.
Keywords: Economic policy; Capitalism -- History -- 20th century; Markets; Economic history -- 1945-; Globalization; Competition, International